DISC1 regulates expression of the neurotrophin VGF through the PI3K/AKT/CREB pathway. (12th August 2015) - Rodríguez‐Seoane, Carmen; Ramos, Adriana; Korth, Carsten; Requena, Jesús R.
Abstract Disrupted in schizophrenia (DISC1) is a risk factor for chronic mental disease. In a previous proteomic study, we reported that knocking down DISC1 results in a sharp decrease in the levels of the neuropeptide precursor VGF (non‐acronymic) and leads to reduced activation of cAMP response element‐binding protein (CREB) and protein kinase B (AKT) in neurons. The main objective of this study is to complete the characterization of the route, or routes, involving AKT and CREB through which DISC1 modulates the expression of VGF. For that we explored known players upstream of AKT and the DISC1 binding partners glycogen synthase kinase‐3 beta and Phosphodiesterase‐4, which might in turn reach out to CREB in murine neuron primary culture. We found that DISC1 modulates the activation of Phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase (PI3K). Furthermore, pharmacological inhibition of PI3K resulted in decreased expression of VGF. All this suggests that the PI3K/AKT pathway plays a role in mediating the effects of DISC1 silencing on VGF expression. Given the important roles of VGF in mental disease, and its drugability, the DISC1‐VGF connection might prove to be important for efforts to develop new therapies for these diseases. <boxed-text content-type="graphic" id="jnc13258-blkfxd-0101" position="anchor" orientation="portrait"> </boxed-text> Our data show that DISC1 regulates the activation state of the PI3K/AKT/CREB signaling route and in turn, contributes to regulate the expression of the neuropeptide precursor VGF in neurons. DISC1 might modulate this molecular pathway by regulating the localization of Grb2 in the cell that promotes the activation of PI3K. Given the important roles of VGF in mental disease, the DISC1‐VGF connection might prove to be important for efforts to develop new therapies for these devastating diseases.